Sleep Deprivation and its Associated Factors Among the Hospitalised Patients - Magar, Sapana Gharti; Shrestha, Sarala (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Sleep is an important factor in maintaining health and wellbeing of an individual. Various factors can lead to poor sleep quality in a patient during hospitalization. Therefore, the purpose of this study was to assess the prevalence of sleep deprivation and its associated factors among the hospitalized patients. Methods: This study was done using descriptive survey design. A total of 65 hospitalized patients were selected for the study using non-probability purposive sampling technique. Informed written consent was taken from each respondent beforehand. Data was collected by interviewing the patients meeting the criteria with pretested semi-structured interview schedule at their bedside by maintaining privacy through bedside curtains. Collected data were analyzed by using descriptive statistics and inferential statistics i.e., chi-square test and Fisher’s exact test. Results: Almost all (98.8%) of respondents had sleep deprivation on the first night of hospitalization which decreased in frequency with increased length of hospital stay. Majority (73.8%) of respondents expressed that hospital environment was disturbing to sleep. Hospital noise (95.8%) and light (66.6%) were reported as the most disturbing factors. Sleep deprivation was associated with hospital environment (p=0.036, p=0.002, p=0.002) on first, second, and third day of hospitalization. This study revealed no significant association of sleep deprivation with age and pain or discomfort of respondents. Conclusions: Hospital environment is the most important factor of sleep deprivation among hospitalized patients, particularly noise and light. Hospital staff should be more careful during the night shift and take measures to minimize noise and lights in the ward to promote sound sleep among patients.